Business Reporting, Transparency, and Accountability in Islamic Microfinance Institutions: Evidence from Baitul Maal wa Tamwil (BMT) - Dedi Irawan; Muhammad Idris (Revenue Journal: Management and Entrepreneurship, 2026)
Baitul Maal wat Tamwil (BMT) as a sharia microfinance institution faces serious challenges in presenting transparent and accountable business reports, especially at the urban micro scale. This study aims to analyze the role of business reports on transparency and accountability and formulate an adaptive reform model. The method used is descriptive qualitative with an intrinsic case study at an urban micro‑BMT in Lampung. Data were collected through semi‑structured interviews, passive observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña (2014) model. The results show that business reports play a positive but not yet optimal role: transparency is limited to physical media without digital channels, accountability operates through the annual member meeting but member participation is very low. The main obstacles include limited human resources, manual information technology, and inconsistent reporting timeliness. The novelty of this study is the Three‑Tier Reporting Model based on the principle of minimum viable transparency that can be adopted by micro‑BMTs throughout Indonesia.